User Generated Content, Firm Generated Content, Celebrity endorser terhadap Kepercayaan Merek pada overclaim Serum Azarine di TikTok - Vivi Gusfiani; Diana Aqmala; Ariati Anomsari; Rudi Kurniawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyse the influence of User generated content (UGC), Firm generated content (FGC), and Celebrity endorser on brand trust with a case study of Azarine's OVERCLAIM Serum product on the TikTok platform. TikTok, as a social media with rapid growth, is a strategic place for companies to utilise creative content so that it can influence brand trust. The research method used is quantitative method. The population of this study were TikTok users and users of Azarine Niacinamide 10% + Dipotassium Glycyrrhizate Glorious Serum products. The sample used was 100 respondents. The sample technique used was purposive sampling which was obtained from distributing online questionnaires. The type of data used are primary and secondary data. The data collected will be analysed through IBM SPSS version 25.0. The results showed that user generated content has a positive and significant effect on brand trust, firm generated content has a significant positive effect on brand trust, and celebrity endorsers have a significant positive effect on brand trust.